Edupreneurship: Utilization of Agricultural Waste As A Medium For Cultivating Volvariella Volvacea Mushrooms - I Made Ardika Yasa; I Made Sutajaya; I Gusti Putu Sudiarta (Syntax Idea)
This article discusses qualitatively descriptive about how edupreneurship utilizes agricultural waste in the Volvariela Volvacea mushroom cultivation business so that it becomes one of the business opportunities. This is one of the follow-up community service activities in the form of dharmatula in Kuranji village, Gerung District, West Lombok Regency, West Nusa Tenggara province related to increasing the effectiveness and productivity of agricultural products by utilizing agricultural waste. With the aim to be able to create jobs, reduce the increase in the amount of agricultural organic waste, increase the value and benefits of agricultural waste, provide education of entrepreneurial spirit to the younger generation. In this case, the author also explains in detail how to breed and market the production results of Volvariela Volvacea mushroom cultivation. In this article also discussed the calculation of production costs and opportunities for the cultivation of Volvariela Volvacea mushrooms so that it can be ascertained that mushrooms have economic value because if carried out properly it only takes 3 months to return the business investment capital. Through edupreneurship, it is also expected to be one of the alternative solutions in overcoming agricultural waste/waste as well as empowering the younger generation to become entrepreneurs.